THE DETERMINANT INFLUENCE OF THE ROLE OF LEADERSHIP VISIONARY ON THE QUALITY OF PRIVATE HIGHER EDUCATION IN MEDAN CITY - Lilik Hidayat Pulungan (State Islamic University of North Sumatra Indonesia, 2019)
The purpose of this study is to determine the contribution of visionary leadership roles which include determining the direction, spokesperson, agents of change and trainers directly on the quality of Private Universities in the city of Medan. Besides determining the factors that have a very dominant influence among the role of visionary leadership on the quality of Private Universities in the city of Medan. This research illustrates the role of a visionary leader in influencing others through his role as a determinant of direction, agents of change, spokespersons and trainers in each situation to achieve the goals of an institution that is a quality university. Through the design of the proposed model, the contribution, and the most dominant factor in influencing the quality of Private Higher Education (Perguruan Tinggi Swasta: PTS) in the city of Medan is illustrated. The research approach used is quantitative, with an explanatory survey methodology through a questionnaire to collect information about the variables studied. The research sample numbered 258, the analysis technique used was Structural Equation Modeling with the analysis phase: (1). Descriptive Analysis, (2). Test data analysis prerequisites, (3). Research Hypothesis Test, (4). Regression Weight and (5). Model Conformity Test and (6). Discussion of Results. From the results of the study note that there is a positive contribution of 0.39 between the role of visionary leadership directly on the quality of private universities in the city of Medan. While the leadership role determining factor contributes 0.57; spokesperson 0.43; the change agent is 0.41 and the trainer is 0.04, so it can be concluded that the most dominant factor influencing the quality of PTS in Medan is the direction determining dimension. Keywords: Leadership, Visionary, Lecturer Performance.